Reliability of Load-Velocity Profiling in Front Crawl Swimming - Olstad, Bjørn Harald; Gonjo, Tomohiro; Njøs, Nikolai; Abächerli, Kathrin; Eriksrud, Ola (Frontiers in Physiology, 2020)
The purposes of this study were to establish test-retest reliability of load-velocity profile outcome measurements in front crawl swimming calculated from three and five different external loads, and if outcome results were comparable between calculation methods. Seven females and eight males performed 25 m semi-tethered swimming with five progressive external loads (females 1,2,3,4 and 5 kg and males 1,3,5,7 and 9 kg) and 50 m front crawl on two different days (all with maximal effort). The mean velocity during three cycles in mid-pool was calculated and plotted as a function of the load to generate the load-velocity profile, expressed as the linear regression. The axes intercepts were defined as the theoretical maximum velocity (V0) and load (L0). The coefficient of determination and the slope of the load-velocity relationship were also calculated. The intra-class correlation coefficient (ICC) showed excellent agreement (ICC ≥ 0.902) for all variables. The coefficient of variation was ≤ 3.14% and typical error was rated as “good” for all variables. A difference was found between the first and second day in V0 from both three and five loads and 50 m front crawl time (p < 0.05), but no difference was found for the other variables, suggesting a systematic change on V0 due to swimmers’ condition. Bland-Altman plots showed small biases for all variables for both the three and five calculation. In conclusion, the load-velocity profile for front crawl swimming can be calculated with high reliability from both five and three external loads to a comparable extent.